2013
DOI: 10.1080/0305764x.2013.837865
|View full text |Cite
|
Sign up to set email alerts
|

Learning and leaving: education and depopulation in an island community

Abstract: This paper probes the extent to which education can be identified as a factor in rural depopulation. The study focuses on the Scottish Hebridean island of Raasay which has seen significant population loss since census records began in 1841. In this study the post-school destinations of all pupils enrolled at Raasay School 1901-2000 have been plotted. In addition, a sample of school pupils from 1941-2000 have been questioned about their decision-making in relation to post-school destinations. The study shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The primary drivers of island population decline and change in Japan are a lack of employment opportunities, with family-related factors playing a role as well (Gillies, 2014). Japan's approach to revitalising peripheral islands faced with a declining and aging population has therefore so far predominantly focused on one-size-fits-all industrial restructuring and, more recently, tourism development (Funck, 2020;Hiraoka et al, 2022;Qu et al, 2023).…”
Section: Creative Revitalisation In Japanese Islandsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary drivers of island population decline and change in Japan are a lack of employment opportunities, with family-related factors playing a role as well (Gillies, 2014). Japan's approach to revitalising peripheral islands faced with a declining and aging population has therefore so far predominantly focused on one-size-fits-all industrial restructuring and, more recently, tourism development (Funck, 2020;Hiraoka et al, 2022;Qu et al, 2023).…”
Section: Creative Revitalisation In Japanese Islandsmentioning
confidence: 99%
“…Islands also represent ideal platforms to test sustainability education, and whether schools can educate about sustainability and at the same time bring revitalisation opportunities to their communities (Yamazumi, 2010). Such initiatives are particularly important in contexts characterised by a declining and aging populations, in which the lack of education and employment opportunities are key factors influencing the out-migration of young individuals from the islands (Gillies, 2014). At the same time, until now initiatives aimed at fostering sustainability through creative education have been scarce and under-researched in the fields of art and education, and even more so within the context of peripheral islands.…”
Section: Island Sustainability Through Creative Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…That is why the outfl ow of young people from rural areas always exceeds the outfl ow from cities. Research conducted in Scotland demonstrates that the youth outfl ow from periphery areas can be signifi cant (Gillies 2014). Argent and Walmsley (2008) showed that in Australia, migration distance and migration frequency depend on the remoteness of the rural peripheral areas from the centres.…”
Section: Previous Researchmentioning
confidence: 99%
“…This process is most often initiated by asymmetries in economic and social opportunities between rural islands and urban and more developed economies, but there are examples where environmental change has been the catalyst ( 9 ). In this self-reinforcing cycle, initial migration of working age people can generate negative feedbacks that further induce migration from communities of origin, including through: economic effects such as reduced investment, market contraction, and diminished supply of goods and services; demographic effects such as increasing age dependency ratios, higher death rates, and lower birth rates; and social effects such as increased loneliness and reduced opportunities for young people to find partners ( 10 13 ). Climate change may add additional stresses that further impel migration, particularly in atolls where sea-level rise, erosion, drought, and storms threaten land, infrastructure, and food and water security.…”
mentioning
confidence: 99%